ANALISA TINGKAT PELAYANAN CHECK-IN DI TERMINAL KEBERANGKATAN DOMESTIK BANDAR UDARA ADISUTJIPTO YOGYAKARTA TERHADAP KEPUASAN PENUMPANG - Hary Soegiri; Kunthari Adzani Putri; Rachmadita Firdauzy Asj’ari (Politeknik Penerbangan Surabaya, 2019)
The aviation services industry in Indonesia has experienced very rapid growth. The more competition in the aviation industry, the more choices of goods or services offered, one of which is to offer the concept of